Comparaison entre espèces chez le primate et évolution du langage - Anne Reboul (Revue de Primatologie)
Language is now specific to modern humans. One of the main problems regarding the evolution of language is that language does not fossilize, which makes it difficult to date its apparition in the homo lineage. However, abilities linked to language or to its use in communication can be evidenced in nonhuman primates, allowing tentative dating through separations between different primate lineages. In addition, primatology data can refute theories regarding the specificity of language to modern humans. Inter-species comparison in primates can thus yield two benefits: fixing the dates for the emergence of some language components and refuting theories about why it is specific to the human species. Thus, inter-species comparison has allowed refuting Lieberman’s hypothesis, linking language specificity to modern humans to the anatomic specificity of their vocal tract. More importantly, one can try to identify in the natural communication of nonhuman primates or in laboratory experiments some components of linguistic communication such as syntax, semantic compositionality, or pragmatics. If syntax seems to be absent, connectivity and negation have been evidenced in laboratory experiments. The existence of semantic compositionality strictly speaking in the natural communication of nonhuman primates is still controversial, but on the other hand, the existence of statistical laws that had been considered as specific to language has been evidenced in the gestural and vocal communication of nonhuman primates. The investigation of nonhuman primates’ communication is a fast-developing research area, that should bring interesting perspectives on language evolution and that would benefit from targeting multimodal (gestures and vocalizations) communication in nonhuman primates.